Evolutionary Origin of the P2X7 C-ter Region: Capture of an Ancient Ballast Domain by a P2X4-Like Gene in Ancient Jawed Vertebrates - Rump, Airi; Smolander, Olli Pekka; Rüütel Boudinot, Sirje; Kanellopoulos, Jean M.; Boudinot, Pierre (Frontiers in Immunology, 2020)
P2X purinergic receptors are extracellular ATP-gated ion channel receptors present on the cell plasma membrane. P2X receptors have been found in Metazoa, fungi, amoebas, and in plants. In mammals, P2X7 is expressed by a large number of cell types and is involved in inflammation and immunity. Remarkably, P2X7 does not desensitize as other P2X do, a feature linked to a “C-cysteine anchor” intra-cytoplasmic motif encoded by exon 11. Another specific feature of P2X7 is its C-terminal cytoplasmic ballast domain (exon 13) which contains a zinc (Zn) coordinating cysteine motif and a GDP-binding region. To determine the origin of P2X7, we analyzed and compared sequences and protein motifs of the C-terminal intra-cytoplasmic region across all main groups of Metazoa. We identified proteins with typical ballast domains, sharing a remarkably conserved Zn-coordinating cysteine motif. Apart from vertebrates, these ballast domains were not associated with a typical P2X architecture. These results strongly suggest that P2X7 resulted from the fusion of a P2X gene, highly similar to P2X4, with an exon encoding a ballast domain. Our work brings new evidence on the origin of the P2X7 purinergic receptor and identifies the Zn-coordinating cysteine domain as the fundamental feature of the ancient ballast fold.